(untitled) (Baghdad Science Journal, 2021)
The study is designed to identify intestinal parasitic infections examined at Al-Aziziyah Hospital in Wasit Governorate in Iraq. In this study, a total of (460) internal and external patients were monitored for intestinal parasitic infections. All stool samples were analyzed by the direct method (microscopic exam.) to discover the trophozoite stages and cyst stages for intestinal protozoan parasites. The most incidence parasites in different sex, area residence and different age groups. Out of (460) patient sample were infected with 217 at a percentage of (47.17%), 101(46.5%) were for males and 116 (53.5%) were for females. It was found that the numbers and percentages of a single (one type of parasite) and double (two type of parasite) infections were 207(95.4 %), 10 (4.6 %) respectively. Intestinal parasitic infections were found in (95.4 %) of the study population (17.9 % 1-5 age). E. histolytica was more common among the positive samples collected from intestinal parasitic species detected in this work. The prevalence of parasitic infection was significantly higher among younger age groups compared with older age groups. The age group 55 years had the highest incidence rate (17.9%) compared with other age groups (7.8%). The distribution of parasitic diseases between rural areas was 66.4% and urban areas was 33.6%.n conclusion, the incidence of intestinal parasitic infection among random sample demands improvement of health education with environmental sanitation and quality of water sources.